Предмет:
АлгебраАвтор:
keelydodsonАвтор:
aimee1.
1) = (х^4 - у^4)(х^4 + у^4) = (х^2 + у^2)(х^2 - у^2)(х^4 + у^4) =(х^4 + у^4)(х^2 + у^2)(х + у)(х - у)
2) = 4х² + 2 = 2(2х² + 1)
3) = (х + у)(1 + х + у + (х + у)²) = (х + у)(1 + х + у + х² + 2ху + у²)
2.
Разложим на множители правую часть:
= (а³ - b³)(а³ + b³) = (a - b)(a² + ab + b²)(a + b)(a² -ab + b²)
Правая часть равна левой
Тождество доказано
Автор:
miloayalaДобавить свой ответ
Предмет:
Английский языкАвтор:
rebeccaОтветов:
Смотреть
Предмет:
Русский языкАвтор:
boosterkennedyОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
shorty0vzaОтветов:
Смотреть
Предмет:
ГеографияАвтор:
hannacortezОтветов:
Смотреть